El oráculo de Delfos, los dioses patrios y la actividad política en Atenas (Argos, 2025)
Like other oracular centres, the sanctuary of Delphi undergoes an evolutional process that leads it to complete integration into the life of the city. In the political life of the city of Athens, its presence is documented at least from the foundation of democracy. Along the 5th century, it demonstrates its evident propensity towards positions opposite to the more popular aspects of the system. The protagonist role of the thetes is subject of derogatory attitudes, like that of those who, more or less directly, share their interests.
Keywords: sanctuaries; oracles; politics; Athens; democracy